An epoxy resin material with nonlinear conductance characteristics and high breakdown field strength, and a preparation method and application thereof

CN123026883APending Publication Date: 2026-11-03ELECTRIC POWER RES INST OF GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611443212.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing nonlinear conductive fillers such as SiC have low nonlinear coefficients in high-pressure and high-power-density scenarios, and the filling amount significantly reduces the mechanical properties and breakdown strength of the material. The threshold electric field is difficult to control, and there is a lack of effective means of equalizing the electric field.

Method used

A cobalt oxide transition layer was constructed on the surface of silicon carbide nanofibers and loaded with silver nanoparticles to form a SiC@Co3O4@Ag gradient heterostructure, which was dispersed in epoxy resin to construct a "spread-hands and shrug-shoulders" double Schottky barrier structure to regulate carrier behavior.

Benefits of technology

Achieving high nonlinear coefficient and high breakdown field strength with low filler content effectively alleviates electric field distortion, improves electric field equalization capability and insulation performance, and meets the application requirements of different voltage levels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123026883A_ABST
    Figure CN123026883A_ABST
Patent Text Reader

Abstract

The application provides an epoxy resin material with nonlinear conductance characteristics and high breakdown field strength, and a preparation method and application thereof, and belongs to the technical field of high-voltage insulation and electronic packaging materials. In the application, silicon carbide nanofibers are used as a matrix, a cobalt oxide transition layer is constructed on the surface of the nanofibers through liquid deposition and high-temperature calcination process, then a sodium citrate reduction method is used to uniformly load silver nanoparticles on the surface of the Co3O4, and a SiC@Co3O4@Ag gradient heterojunction structure is formed. The gradient heterojunction nanofibers are further dispersed in an epoxy resin system, and a nonlinear conductive dielectric epoxy resin composite material is prepared through curing. The preparation process of the application is simple, excellent nonlinear conductive performance and electric field equalization ability can be obtained at a low filler content, and the application has a relatively high breakdown strength, and can be used for electrostatic protection of power semiconductor devices and voltage equalization materials of high-voltage electrical insulation equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of high voltage insulation and electronic packaging materials, and particularly relates to an epoxy resin material with both nonlinear conductivity and high breakdown field strength, its preparation method and application. Background Technology

[0002] The rapid development of high-voltage direct current (HVDC) transmission technology and power semiconductor devices has placed increasingly stringent demands on the performance of electrical insulation materials and electronic packaging materials. In high-voltage power equipment and power modules, factors such as electrode structure, differences in material dielectric constants, and space charge injection often lead to severe local electric field distortion, resulting in insulation failures such as discharge and breakdown. To address this, functionally graded materials (FGMs) with nonlinear conductivity have emerged. These materials can maintain high impedance under low electric fields to preserve insulation performance, and automatically increase conductivity under high electric fields to achieve a uniform electric field distribution, thus achieving adaptive control of electric field stress. They are widely regarded as one of the effective ways to solve the problem of electric field concentration.

[0003] Currently, commonly used nonlinear conductive fillers mainly include semiconductor particles or fibers such as silicon carbide (SiC) and zinc oxide (ZnO). Among them, SiC is widely used in the preparation of epoxy resin-based nonlinear conductive composite materials due to its good thermal stability, moderate nonlinear characteristics, and relatively low dielectric constant. However, there are still many shortcomings in the existing technology: First, the nonlinear coefficient provided by a single SiC filler is low (usually α<10), and the voltage equalization effect is limited, making it difficult to meet the voltage equalization requirements in ultra-high voltage and high power density scenarios; Second, to obtain sufficient nonlinear conductivity, a high filler content (>30 vol%) is often required, which not only significantly reduces the mechanical properties and processing flowability of the composite material, but also causes a sharp drop in breakdown strength due to filler agglomeration; Third, the threshold electric field of the composite material mainly depends on the properties of the filler itself, and there is a lack of effective control methods to adapt to the application requirements of different voltage levels.

[0004] In recent years, researchers have attempted to improve the filler / matrix interface properties through surface modification and heterostructure design, aiming to enhance nonlinear conductivity. For example, coating SiO2 or Al2O3 insulating layers on the SiC surface can suppress leakage current under low electric fields, but it also weakens the conductivity response speed under high electric fields. Although metal nanoparticle modification of semiconductor fillers can enhance the local field enhancement effect, its ability to regulate carrier transport remains limited due to the limitations of a single interface structure, and it also faces the problem of breakdown strength degradation at higher filler contents. Therefore, how to simultaneously achieve high nonlinear coefficients, tunable threshold electric fields, and excellent breakdown strength at low filler contents has become a pressing technical challenge in this field. Summary of the Invention

[0005] To address the problems of insufficient nonlinear conductivity, difficulty in controlling the threshold electric field, and degradation of dielectric and mechanical properties due to high filling in existing electric field equalization materials, this invention proposes an epoxy resin material with both nonlinear conductivity and high breakdown field strength, as well as its preparation method and application.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing an epoxy resin material that combines nonlinear conductivity and high breakdown field strength, comprising the following steps: (1) Disperse silicon carbide (SiC) nanofibers in an organic solvent and sonicate them to obtain a suspension; add cobalt salt solution to the suspension and carry out liquid phase deposition reaction under alkaline conditions. After the reaction is completed, separate solid and liquid, dry, and then calcine at high temperature in air atmosphere to obtain cobalt oxide coated silicon carbide nanofibers (SiC@Co3O4). (2) The cobalt oxide-coated silicon carbide nanofibers obtained in step (1) are dispersed in water, silver salt and reducing agent are added, and a reduction reaction is carried out under alkaline conditions so that silver nanoparticles are loaded on the surface of the cobalt oxide layer. After the reaction is completed, solid-liquid separation, washing and drying are performed to obtain modified silicon carbide nanofibers (SiC@Co3O4@Ag nanofibers) with a cobalt oxide transition layer and a silver nanoparticle outer layer. (3) The modified silicon carbide nanofibers obtained in step (2) are dispersed in an organic solvent, mixed with epoxy resin and heated and stirred until the solvent is completely evaporated. Then, a curing agent and an accelerator are added, and the mixture is mixed, degassed and cured to obtain the epoxy resin material.

[0007] Further, in step (1), the cobalt salt is cobalt nitrate (Co(NO3)2), and in the liquid phase deposition reaction, the system pH is controlled at 8.5, the reaction temperature is 70℃, and the reaction time is 5h; the heating rate of the high-temperature calcination is 5.5℃·min. -1 The calcination temperature is 600℃ and the holding time is 4.5h.

[0008] Further, in step (1), the ratio of the amount of silicon carbide nanofibers to the amount of cobalt salt in the cobalt salt solution is 2g:0.05mol, and the volume ratio of the cobalt salt solution to the suspension is (10-50):200.

[0009] Further, in step (2), the silver salt is silver nitrate (AgNO3), the reducing agent is sodium citrate, and the pH value of the system in the reduction reaction is controlled at 12.

[0010] Further, in step (2), the mass ratio of the cobalt oxide-coated silicon carbide nanofibers to the reducing agent is 1:0.9, and silver salt is added to make the silver ion concentration in the system 10 mmol / L.

[0011] Further, in step (3), the epoxy resin is a bisphenol A type epoxy resin, the curing agent is methylhexahydrophthalic anhydride (MHHPA), and the accelerator is 2-ethyl-4-methylimidazolium (EMI); the curing molding adopts a step-by-step temperature-increasing curing program, which is 100℃ for 1 hour, 115℃ for 1 hour, and 135℃ for 1 hour in sequence.

[0012] Further, in step (3), the volume fraction of the modified silicon carbide nanofibers in the epoxy resin material is 1 vol% to 4 vol%, and the mass ratio of the epoxy resin, curing agent and accelerator is 10:9:0.1.

[0013] For example, the preparation method of the epoxy resin material with both nonlinear conductivity and high breakdown field strength in this invention specifically includes the following steps: (1) 2g of SiC nanofibers were dispersed in 200mL of isopropanol and sonicated at medium power for 30min to obtain a uniform and stable SiC suspension. Meanwhile, 0.05mol of Co(NO3)2·6H2O was dissolved in deionized water to prepare 90mL of cobalt nitrate solution. Then, 40mL of deionized water was added to the SiC suspension under continuous stirring and stirring was continued for 20min. After that, the cobalt nitrate solution was slowly added dropwise to the SiC suspension and reacted in an oil bath at 70℃ for 5h. During the reaction, the pH of the system was maintained at 8.5 by adding ammonia dropwise. After the reaction was completed, the precursor obtained was collected by vacuum filtration and dried at 80℃ for 12h. Then, it was processed at 5.5℃·min -1 The temperature was increased to 600℃ at a heating rate, held for 4.5 h, and then naturally cooled to room temperature to obtain Co3O4-coated SiC nanofibers, denoted as SiC@Co3O4. (2) Disperse 2g of SiC@Co3O4 obtained in step (1) in 100mL of deionized water and sonicate for at least 30min to avoid particle agglomeration. Then add AgNO3 to make Ag + Concentration reached 10 mmol·L -1 1.8 g of sodium citrate was added under continuous stirring. Since the morphology of Ag nanoparticles is affected by the pH of the solution, NaOH solution was slowly added dropwise to adjust the pH of the system to 12, thereby obtaining spherical Ag nanoparticles and promoting Ag... +After the reduction deposition on the SiC@Co3O4 surface, the product was allowed to stand for 30 min, then vacuum filtered and washed with deionized water to remove residual organic matter. Finally, the product was freeze-dried for 12 h to obtain modified silicon carbide nanofibers, denoted as SiC@Co3O4@Ag nanofibers.

[0014] (3) SiC@Co3O4@Ag nanofibers (added at a volume fraction of 1 vol% to 4 vol% in the epoxy resin material) were dispersed in N,N-dimethylformamide (DMF) and sonicated for 30 min. Then, the resulting dispersion was mixed with 10 g of bisphenol A type epoxy resin and stirred at 120 °C for 2 h to ensure uniform dispersion of SiC@Co3O4@Ag nanofibers in the epoxy resin. After the DMF was completely volatilized, 9 g of methylhexahydrophthalic anhydride (MHHPA) and 0.1 g of [unclear text - possibly a continuation of the previous sentence] were added. 2-Ethyl-4-methylimidazole (EMI) was thoroughly mixed under magnetic stirring. The resulting mixture was then placed in a 70°C vacuum oven for continuous vacuum degassing for 15 minutes to remove entrained air bubbles. Finally, the mixture was poured into a polytetrafluoroethylene (PTFE) mold and cured using a step-by-step temperature curing procedure: 100°C for 1 hour, 115°C for 1 hour, and 135°C for 1 hour, ultimately yielding an epoxy resin material.

[0015] The present invention also provides an epoxy resin material with both nonlinear conductivity and high breakdown field strength prepared according to the above preparation method.

[0016] Furthermore, the epoxy resin material comprises an epoxy resin matrix and modified silicon carbide nanofibers dispersed in the epoxy resin matrix; the modified silicon carbide nanofibers, from the inside out, consist of a silicon carbide nanofiber core layer, a cobalt oxide transition layer, and a silver nanoparticle outer layer, forming a SiC@Co3O4@Ag gradient heterostructure.

[0017] Furthermore, in the gradient heterostructure, silicon carbide, cobalt oxide, and silver exhibit progressively varying work functions and band structures, forming gradient band bending and a built-in electric field at the heterostructure interface, thus constituting an asymmetric double Schottky barrier structure; the Co in the cobalt oxide transition layer... 2+ and Co 3+ Two valence states coexist, with the silver nanoparticles loaded on the surface of the cobalt oxide transition layer in a metallic state.

[0018] Furthermore, the modified silicon carbide nanofibers simultaneously contain the (110) crystal plane of silicon carbide, the (222) crystal plane of cobalt oxide, and the (200) crystal plane of silver; the cobalt oxide and silver nanoparticles are uniformly dispersed on the surface of the silicon carbide nanofibers.

[0019] The present invention also provides an application of the above-mentioned epoxy resin material with both nonlinear conductivity and high breakdown field strength in voltage equalization materials for high voltage electrical insulation equipment or electrostatic protection materials for power semiconductor devices.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects: This invention uses silicon carbide (SiC) nanofibers as a matrix, constructing a cobalt oxide (Co3O4) transition layer on its surface through liquid phase deposition and high-temperature calcination. Subsequently, silver (Ag) nanoparticles are uniformly loaded onto the Co3O4 surface using a sodium citrate reduction method, forming a SiC@Co3O4@Ag gradient heterostructure. The gradient heterostructure nanofibers are further dispersed in an epoxy resin system, and cured to obtain a nonlinear conductive dielectric epoxy resin composite material. Due to the progressively changing work function and band structure between SiC, Co3O4, and Ag, the interface electrons are redistributed, forming gradient band bending and a built-in electric field at the multi-level heterostructure interface, thus constructing a novel "shruggie-like" double Schottky barrier structure. This structure can effectively control the injection and transport behavior of charge carriers, enabling the composite material to maintain high resistance and excellent insulation performance under low electric fields, and rapidly establish conductive channels under high electric fields, achieving reversible switching between conductive and insulating states, effectively mitigating local electric field distortion and space charge accumulation. The present invention has a simple preparation process and can obtain excellent nonlinear conductivity and electric field equalization ability with low filler content, while also having high breakdown strength. It can be used as an electrostatic protection material for power semiconductor devices and an equalization material for high voltage electrical insulation equipment. Attached Figure Description

[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 The images show the Fourier Transform Infrared (FTIR) spectra of SiC nanofibers before and after modification in Example 1. Figure 2 The images show the X-ray diffraction (XRD) patterns of SiC nanofibers before and after modification in Example 1. Figure 3 In Example 1, a is the XPS full spectrum of SiC nanofibers and SiC@Co3O4@Ag nanofibers; b is the high-resolution XPS spectrum of Co element in SiC@Co3O4@Ag nanofibers; and c is the high-resolution XPS spectrum of Ag element in 3% SiC@30-Co3O4@Ag prepared in Example 1. Figure 4Image a is a transmission electron microscope (TEM) image of SiC@Co3O4@Ag nanofibers in Example 1; image b is a high-resolution transmission electron microscope (HRTEM) image; image c is a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image of SiC@Co3O4@Ag nanofibers; image d is an elemental plane distribution diagram of C, Si, Co, O, and Ag elements in SiC@Co3O4@Ag nanofibers. Figure 5 Scanning electron microscope (SEM) images of SiC nanofibers and SiC@Co3O4@Ag nanofibers in Example 1: a is a low-magnification morphology image of SiC nanofibers, b is a high-magnification morphology image of SiC nanofibers; c is a low-magnification morphology image of SiC@Co3O4@Ag nanofibers, and d is a high-magnification morphology image of SiC@Co3O4@Ag nanofibers. Figure 6 In Example 1, a represents the conductivity-electric field (σ-E) nonlinear characteristic curves of SiC nanofibers, SiC@Co3O4 nanofibers, and SiC@Co3O4@Ag nanofibers; b represents the σ-E nonlinear characteristic curves of epoxy resin materials with different Co3O4 shell thicknesses in Examples 1-3; and c represents the σ-E nonlinear characteristic curves of epoxy resin materials with different SiC@Co3O4@Ag nanofiber volume fractions in Examples 1, 4-6. Figure 7 The breakdown field strength characteristics of the epoxy resin materials in Examples 1, 4-6 and Comparative Examples 1-5 are shown, where a is the 3% SiC material in Comparative Example 1; b is the epoxy resin materials with different SiC@Co3O4 volume fractions in Comparative Examples 2-5; and c is the epoxy resin materials with different SiC@Co3O4@Ag nanofiber volume fractions in Examples 1, 4-6. Detailed Implementation

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0024] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0025] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0026] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0027] All raw materials used in the embodiments of this invention were commercially available. Specifically, bisphenol A epoxy resin, N,N-dimethylformamide (DMF), methylhexahydrophthalic anhydride (MHHPA), 2-ethyl-4-methylimidazolium (EMI), and sodium citrate were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Silver nitrate (AgNO3) was purchased from Shenzhen Bolianda Technology Co., Ltd. SiC nanofibers (approximately 100 nm in diameter and 10-20 μm in length) were purchased from Fenghui Nanotechnology Co., Ltd.

[0028] The technical solution of the present invention will be further illustrated by the following embodiments.

[0029] Example 1 (1) 2g of SiC nanofibers were dispersed in 200mL of isopropanol and sonicated at medium power for 30min to obtain a uniform and stable SiC suspension. Simultaneously, 0.05mol of Co(NO3)2·6H2O was dissolved in 50mL of deionized water. Then, 40mL of deionized water was added under continuous stirring, and stirring was continued for 20min to prepare a 90mL cobalt nitrate solution. Afterward, 30mL of the cobalt nitrate solution was slowly added dropwise to the SiC suspension, and the reaction was carried out in a 70℃ oil bath for 5h. During the reaction, the pH of the system was maintained at 8.5 by adding ammonia dropwise. After the reaction, the precursor was collected by vacuum filtration and dried at 80℃ for 12h, then processed at 5.5℃·min. -1The temperature was increased to 600℃ at a heating rate, held for 4.5 h, and then naturally cooled to room temperature to obtain Co3O4-coated SiC nanofibers, denoted as SiC@Co3O4. (2) Disperse 2g of SiC@Co3O4 obtained in step (1) in 100mL of deionized water and sonicate for at least 30min to avoid particle agglomeration. Then add AgNO3 to make Ag + Concentration reached 10 mmol·L -1 1.8 g of sodium citrate was added under continuous stirring. Since the morphology of Ag nanoparticles is affected by the pH of the solution, NaOH solution was slowly added dropwise to adjust the pH of the system to 12, thereby obtaining spherical Ag nanoparticles and promoting Ag... + After the reduction deposition on the SiC@Co3O4 surface, the product was allowed to stand for 30 min, then vacuum filtered and washed with deionized water to remove residual organic matter. Finally, the product was freeze-dried for 12 h to obtain modified silicon carbide nanofibers, denoted as SiC@Co3O4@Ag nanofibers.

[0030] (3) SiC@Co3O4@Ag nanofibers (1.64g was added to make its volume fraction in the epoxy resin material 3 vol%) were dispersed in N,N-dimethylformamide (DMF) and sonicated for 30 min. Then the resulting dispersion was mixed with 10g of bisphenol A type epoxy resin and stirred at 120℃ for 2 h to ensure uniform dispersion of SiC@Co3O4@Ag nanofibers in epoxy resin. After the DMF was completely volatilized, 9g of methylhexahydrophthalic anhydride (MHHPA) and 0.1g of [unspecified substance] were added. 2-Ethyl-4-methylimidazole (EMI) was mixed thoroughly under magnetic stirring. The resulting mixture was then placed in a 70°C vacuum oven for 15 minutes to remove entrained air bubbles. Finally, the mixture was poured into a polytetrafluoroethylene (PTFE) mold and cured using a stepwise temperature curing procedure: 100°C for 1 hour, 115°C for 1 hour, and 135°C for 1 hour. The resulting epoxy resin material with a thickness of 0.5 mm was denoted as 3%SiC@30-Co3O4@Ag (where 3% represents the volume fraction of SiC@Co3O4@Ag nanofibers in the epoxy resin material as 3 vol%, and 30 represents the volume of cobalt nitrate solution used as 30 mL).

[0031] Example 2 Same as Example 1, except that 0.05 mol Co(NO3)2·6H2O was dissolved in 50 mL of deionized water, and then 40 mL of deionized water was added under continuous stirring, and stirring was continued for 20 min to prepare 90 mL of cobalt nitrate solution. 10 mL of cobalt nitrate solution was used for subsequent preparation, and the remaining steps were consistent with Example 1. The obtained epoxy resin material was denoted as 3%SiC@10-Co3O4@Ag.

[0032] Example 3 Same as Example 1, except that 0.05 mol Co(NO3)2·6H2O was dissolved in 50 mL of deionized water, and then 40 mL of deionized water was added under continuous stirring, and stirring was continued for 20 min to prepare 90 mL of cobalt nitrate solution. 50 mL of cobalt nitrate solution was used for subsequent preparation, and the remaining steps were consistent with Example 1. The obtained epoxy resin material was denoted as 3%SiC@50-Co3O4@Ag.

[0033] Example 4 Same as Example 1, except that in step (3), 1.08g of SiC@Co3O4@Ag nanofibers were added to make its volume fraction in the epoxy resin material 2 vol%. The rest of the steps are the same as in Example 1. The resulting epoxy resin material is denoted as 2%SiC@30-Co3O4@Ag.

[0034] Example 5 Same as Example 1, except that in step (3), 2.21g of SiC@Co3O4@Ag nanofibers were added to make its volume fraction in the epoxy resin material 4 vol%. The rest of the steps are the same as in Example 1. The resulting epoxy resin material is denoted as 4%SiC@30-Co3O4@Ag.

[0035] Example 6 Same as Example 1, except that in step (3), 0.53g of SiC@Co3O4@Ag nanofibers are added to make its volume fraction in the epoxy resin material 1 vol%. The rest of the steps are the same as in Example 1. The resulting epoxy resin material is denoted as 1%SiC@30-Co3O4@Ag.

[0036] Comparative Example 1 SiC nanofibers (1.64g added to make its volume fraction in epoxy resin material 3 vol%) were dispersed in N,N-dimethylformamide (DMF) and sonicated for 30 min. The resulting dispersion was then mixed with 10g of bisphenol A type epoxy resin and stirred at 120℃ for 2 h. After the DMF was completely volatilized, 9g of methylhexahydrophthalic anhydride (MHHPA) and 0.1g of 2-ethyl-4-methylimidazole (EMI) were added and mixed thoroughly under magnetic stirring. The resulting mixture was then placed in a 70℃ vacuum oven for continuous vacuum degassing for 15 min to remove entrained air bubbles. Finally, the mixture was poured into a polytetrafluoroethylene (PTFE) mold and cured using a stepwise temperature curing program: 100℃ for 1 h, 115℃ for 1 h, and 135℃ for 1 h. The resulting epoxy resin material was denoted as 3% SiC.

[0037] Comparative Example 2 (1) 2g of SiC nanofibers were dispersed in 200mL of isopropanol and sonicated at medium power for 30min to obtain a uniform and stable SiC suspension. Simultaneously, 0.05mol of Co(NO3)2·6H2O was dissolved in 50mL of deionized water. Then, 40mL of deionized water was added under continuous stirring, and stirring was continued for 20min to prepare a 90mL cobalt nitrate solution. Afterward, 30mL of the cobalt nitrate solution was slowly added dropwise to the SiC suspension, and the reaction was carried out in a 70℃ oil bath for 5h. During the reaction, the pH of the system was maintained at 8.5 by adding ammonia dropwise. After the reaction, the precursor was collected by vacuum filtration and dried at 80℃ for 12h, then processed at 5.5℃·min. -1 The temperature was increased to 600℃ at a heating rate, held for 4.5 h, and then naturally cooled to room temperature to obtain Co3O4-coated SiC nanofibers, denoted as SiC@Co3O4. (2) SiC@Co3O4 (1.64g was added to make its volume fraction in the epoxy resin material 3 vol%) was dispersed in N,N-dimethylformamide (DMF) and sonicated for 30 min. Then the resulting dispersion was mixed with 10g of bisphenol A type epoxy resin and stirred at 120℃ for 2 h. After the DMF was completely volatilized, 9g of methylhexahydrophthalic anhydride (MHHPA) and 0.1g of 2-ethyl-4-methylimidazole (EMI) were added and mixed thoroughly under magnetic stirring. Then the resulting mixture was placed in a vacuum oven at 70℃ and continuously vacuumed for 15 min to remove the bubbles entrained in the system. Finally, the mixture was poured into a polytetrafluoroethylene (PTFE) mold and cured using a step-by-step temperature curing program: 100℃ for 1 h, 115℃ for 1 h, and 135℃ for 1 h. The epoxy resin material was finally obtained and denoted as 3%SiC@Co3O4.

[0038] Comparative Example 3 Similar to Comparative Example 2, the only difference is that in step (2), the amount of SiC@Co3O4 added is 0.53g, so that its volume fraction in the epoxy resin material is 1vol%. The rest of the steps are the same as those in Comparative Example 2, and the resulting epoxy resin material is recorded as 1%SiC@Co3O4.

[0039] Comparative Example 4 Similar to Comparative Example 2, the only difference is that in step (2), the amount of SiC@Co3O4 added is 1.08g, so that its volume fraction in the epoxy resin material is 2vol%. The rest of the steps are the same as those in Comparative Example 2, and the resulting epoxy resin material is recorded as 2%SiC@Co3O4.

[0040] Comparative Example 5 Similar to Comparative Example 2, the only difference is that in step (2), the amount of SiC@Co3O4 added is 2.21g, so that its volume fraction in the epoxy resin material is 4vol%. The rest of the steps are the same as those in Comparative Example 2, and the resulting epoxy resin material is recorded as 4%SiC@Co3O4.

[0041] Performance testing Figure 1 The images show the Fourier Transform Infrared (FTIR) spectra of SiC nanofibers before and after modification in Example 1. The results indicate that the characteristic peak of SiC after loading (797 cm⁻¹) is... -1 It remains unchanged, while it is located at 667 cm. -1 The Co-O vibrational peak at 1442 cm⁻¹ was observed in both SiC@Co₃O₄ and SiC@Co₃O₄@Ag samples. Notably, the peak at 1442 cm⁻¹ appeared only in the SiC@Co₃O₄@Ag sample. -1 A new absorption peak was observed, corresponding to CO3 adsorbed on the surface of Ag nanoparticles. 2- .

[0042] X-ray diffraction (XRD) is used to analyze the crystal structure of a sample. Figure 2 The X-ray diffraction (XRD) patterns of SiC nanofibers before and after modification in Example 1 show that SiC, SiC@Co3O4, and SiC@Co3O4@Ag all exhibit clear diffraction peaks. Specifically, the characteristic diffraction peaks of Co3O4 (PDF#78-1970) correspond to the (220), (311), (222), and (440) crystal planes, respectively; while the characteristic peaks of Ag (PDF#87-0597) correspond to the (111), (200), (220), and (311) crystal planes.

[0043] Figure 3Image a shows the XPS full spectrum of SiC nanofibers and SiC@Co3O4@Ag nanofibers in Example 1; image b shows the high-resolution XPS spectrum of Co element in SiC@Co3O4@Ag nanofibers; and image c shows the high-resolution XPS spectrum of Ag element in 3% SiC@30-Co3O4@Ag prepared in Example 1. It can be seen that the SiC@Co3O4@Ag material simultaneously contains characteristic peaks of Si, C, O, Co, and Ag elements, proving that Co3O4 and Ag have been successfully introduced into the composite system. Further analysis of the high-resolution Co 2p spectrum reveals that the Co 2p3 / 2 and Co 2p1 / 2 peaks are located at approximately 782 eV and 797 eV, respectively, accompanied by significant satellite peaks (Sat), indicating the presence of Co in the material. 2+ and Co 3+ The coexistence of two valence states further confirms the successful formation of Co3O4 with a mixed valence structure. Figure 3 In the middle c, the high-resolution Ag 3d spectrum is shown, where the Ag 3d5 / 2 and Ag 3d3 / 2 peaks are located at approximately 368 eV and 374 eV, respectively, corresponding to metallic Ag, indicating that Ag exists in the composite system in the form of nanoparticles.

[0044] Figure 4 Image a shows a transmission electron microscope (TEM) image of SiC@Co3O4@Ag nanofibers in Example 1; image b shows a high-resolution transmission electron microscope (HRTEM) image; image c shows a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image of SiC@Co3O4@Ag nanofibers; image d shows the elemental plane distribution of C, Si, Co, O, and Ag elements in SiC@Co3O4@Ag nanofibers. The TEM images further demonstrate the spatial distribution of Co3O4 and Ag nanoparticles on the surface of SiC nanofibers (see...). Figure 4 (a) High-resolution TEM image (see Figure 4 As shown in Figure b), the interplanar spacings are 0.156 nm, 0.226 nm, and 0.203 nm, corresponding to the (110) crystal plane of SiC, the (222) crystal plane of Co3O4, and the (200) crystal plane of Ag. These results are highly consistent with the XRD analysis results, further proving that all components have been successfully constructed in the composite system. Meanwhile, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images visually demonstrate that cobalt tetroxide and silver nanoparticles can be uniformly and stably loaded onto the surface of silicon carbide nanofibers (see Figure b). Figure 4 c). Elemental surface distribution characterization results (see...) Figure 4 (d) further corroborates that the Co3O4 and Ag components are uniformly dispersed on the surface of the silicon carbide matrix.

[0045] Figure 5Scanning electron microscope (SEM) images of SiC nanofibers and SiC@Co3O4@Ag nanofibers from Example 1 are shown: a) low-magnification morphology of SiC nanofibers; b) high-magnification morphology of SiC nanofibers; c) low-magnification morphology of SiC@Co3O4@Ag nanofibers; and d) high-magnification morphology of SiC@Co3O4@Ag nanofibers. The SEM images demonstrate that Co3O4 and Ag nanoparticles are uniformly loaded onto the surface of the SiC nanofibers.

[0046] In summary, Example 1 of this invention successfully constructed SiC@Co3O4@Ag nanofibers with a well-defined gradient heterojunction interface, providing a stable heterojunction structure for enhancing interfacial charge regulation and improving electron transport performance.

[0047] Table 1 shows the threshold field strength and nonlinear coefficient of each epoxy resin material in the examples and comparative examples.

[0048] Table 1 Figure 6 In Example 1, a represents the conductivity-electric field (σ-E) nonlinear characteristic curves of SiC nanofibers, SiC@Co3O4 nanofibers, and SiC@Co3O4@Ag nanofibers; b represents the σ-E nonlinear characteristic curves of epoxy resin materials with different Co3O4 shell thicknesses in Examples 1-3; and c represents the σ-E nonlinear characteristic curves of epoxy resin materials with different SiC@Co3O4@Ag nanofiber volume fractions in Examples 1, 4-6.

[0049] Figure 6 Table a shows the nonlinear conductivity (σ)-electric field (E) characteristics of epoxy resin-based electric field gradient materials (FGMs) before and after Co3O4 coating and Ag loading. By fitting the nonlinear conductivity-electric field curves, two key parameters determining the electric field gradient performance were extracted: the nonlinear coefficient (α) and the threshold electric field (Es). The results are shown in Table 1. (Combined with Table 1 and...) Figure 6It can be seen that compared with FGMs filled with original SiC nanofibers, the introduction of Co3O4 and Ag nanoparticles significantly improves both the nonlinear coefficient and threshold electric field of the material. Specifically, after Co3O4 coating and Ag loading, the nonlinear coefficient of the FGMs increases from 5.9 in the SiC system to 12.8 in the SiC@Co3O4@Ag system, while the threshold electric field increases from 1.19 kV / mm to approximately 1.50 kV / mm, indicating a significant enhancement in the material's electric field response capability. This performance improvement is mainly attributed to the construction of the SiC-Co3O4-Ag gradient barrier interface. The "shruggie-like" double Schottky barrier structure significantly increases the barrier height of the SiC-Co3O4 interface and the Co3O4-Ag interface, thereby forming a spatially asymmetric double barrier structure, realizing the stepwise control of carrier transport.

[0050] Figure 6 Further, it is shown in Figure b that the threshold electric field of the material can be effectively adjusted by controlling the thickness of the Co3O4 shell. When x=10 (i.e., Example 2, the amount of cobalt nitrate solution used is 10 mL), the Es of the epoxy resin material is 1.46 kV / mm; when x=30 (i.e., Example 1), Es increases to 1.50 kV / mm; and when x=50 (i.e., Example 3), it further increases to 1.85 kV / mm. This indicates that a thicker Co3O4 layer not only enhances the asymmetry of the "shruggie-like" double barrier structure, improving the overall barrier height and electric field suppression capability, but also introduces more Co3O4 particles and interface traps, which can trap electrons under low electric field conditions. This variation is consistent with the test results in single nanofibers.

[0051] In addition, such as Figure 6 As shown in Figure c, with the increase of SiC@Co3O4@Ag nanofiber content, percolation conductive pathways gradually form inside the epoxy resin material, thereby reducing the switching electric field. Notably, even at lower filler contents (3 vol% and 4 vol%), the system still achieves a nonlinear coefficient exceeding 12 without the need for pre-constructing a conductive network. This further demonstrates that the "shruggie-like" double-barrier structure can effectively maintain electric field gradient modulation capabilities at the macroscopic composite material scale, providing reliable protection for electric field equalization and electrostatic discharge (ESD) protection.

[0052] Figure 7The breakdown field strength characteristics of the epoxy resin materials in Examples 1, 4-6, and Comparative Examples 1-5 are shown. Here, a is the 3% SiC material in Comparative Example 1; b is the epoxy resin materials with different SiC@Co3O4 volume fractions in Comparative Examples 2-5; and c is the epoxy resin materials with different SiC@Co3O4@Ag nanofiber volume fractions in Examples 1, 4-6. It can be seen that when the filler volume fraction is only 2 vol%, the breakdown strength of the material is as high as 68.72 kV / mm, and when the filler volume fraction is 3 vol%, the breakdown strength reaches 29.96 kV / mm, which is 260% higher than that of pure EP / SiC.

[0053] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing an epoxy resin material possessing both nonlinear conductivity and high breakdown field strength, characterized in that, Includes the following steps: (1) Disperse silicon carbide nanofibers in an organic solvent and sonicate them to obtain a suspension; add cobalt salt solution to the suspension and carry out liquid phase deposition reaction under alkaline conditions. After the reaction is completed, separate solid and liquid, dry, and then calcine at high temperature in air atmosphere to obtain cobalt oxide coated silicon carbide nanofibers. (2) The cobalt oxide-coated silicon carbide nanofibers are dispersed in water, silver salt and reducing agent are added, and a reduction reaction is carried out under alkaline conditions so that silver nanoparticles are loaded on the surface of the cobalt oxide layer. After the reaction is completed, the silicon carbide nanofibers with a cobalt oxide transition layer and a silver nanoparticle outer layer are obtained by solid-liquid separation, washing and drying. (3) The modified silicon carbide nanofibers are dispersed in an organic solvent, mixed with epoxy resin and heated and stirred until the solvent is completely evaporated. Then, a curing agent and an accelerator are added, and the mixture is mixed, degassed and cured to obtain the epoxy resin material.

2. The method for preparing the epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 1, characterized in that, In step (1), the cobalt salt is cobalt nitrate; in the liquid phase deposition reaction, the system pH is controlled at 8.5, the reaction temperature is 70℃, and the reaction time is 5h; the heating rate of the high-temperature calcination is 5.5℃·min. -1 The calcination temperature is 600℃ and the holding time is 4.5h.

3. The method for preparing the epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 1, characterized in that, In step (1), the ratio of the amount of silicon carbide nanofibers to the amount of cobalt salt in the cobalt salt solution is 2g:0.05mol, and the volume ratio of the cobalt salt solution to the suspension is (10-50):

200.

4. The method for preparing the epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 1, characterized in that, In step (2), the silver salt is silver nitrate, the reducing agent is sodium citrate, and the pH value of the system in the reduction reaction is controlled at 12.

5. The method for preparing the epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 1, characterized in that, In step (2), the mass ratio of the cobalt oxide-coated silicon carbide nanofibers to the reducing agent is 1:0.9, and silver salt is added to make the silver ion concentration in the system 10 mmol / L.

6. The method for preparing the epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 1, characterized in that, In step (3), the epoxy resin is bisphenol A type epoxy resin, the curing agent is methylhexahydrophthalic anhydride, and the accelerator is 2-ethyl-4-methylimidazolium; the curing molding adopts a step-by-step temperature-increasing curing program, which is 100℃ for 1 hour, 115℃ for 1 hour, and 135℃ for 1 hour in sequence.

7. The method for preparing the epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 1, characterized in that, In step (3), the volume fraction of the modified silicon carbide nanofibers in the epoxy resin material is 1 vol% to 4 vol%, and the mass ratio of the epoxy resin, curing agent and accelerator is 10:9:0.

1.

8. An epoxy resin material with both nonlinear conductivity and high breakdown field strength prepared by the preparation method according to any one of claims 1 to 7.

9. The epoxy resin material with both nonlinear conductivity and high breakdown field strength according to claim 8, characterized in that, The epoxy resin material comprises an epoxy resin matrix and modified silicon carbide nanofibers dispersed in the epoxy resin matrix; the modified silicon carbide nanofibers, from the inside out, include a silicon carbide nanofiber core layer, a cobalt oxide transition layer, and a silver nanoparticle outer layer, forming a SiC@Co3O4@Ag gradient heterostructure.

10. The application of an epoxy resin material with both nonlinear conductivity and high breakdown field strength as described in any one of claims 8 to 9 in voltage equalization materials for high-voltage electrical insulation equipment or electrostatic protection materials for power semiconductor devices.